Holistic View of ALK TKI Resistance in ALK-Positive Anaplastic Large Cell Lymphoma - Wang, Yuan; He, Jing; Xu, Manyu; Xue, Qingfeng; Zhu, Cindy; Liu, Juan; Zhang, Yaping; Shi, Wenyu (Frontiers in Oncology, 2022)
Anaplastic large cell lymphoma kinase (ALK) is a receptor tyrosine kinase (RTK), which is mainly expressed through the ectopic expression of carcinogenesis. It plays a key role in the occurrence of Anaplastic lymphoma kinase-expressing T-cell lymphoma (ALK+ ALCL). Therefore, it is considered to be the main therapeutic target of ALK+ ALCL. The application of ALK-TKI (ALK Tyrosine Kinase Inhibitor) has greatly improved the therapeutic effect of ALK+ALCL patients, but the emergence of drug resistance is still unavoidable and the application of ALK inhibitors is also greatly restricted. Although various mechanisms of ALK-TKI resistance have been discovered, the problem of resistance has not been completely solved. More importantly, there are relatively few clinical studies of AlK-TKI resistance . Therefore, this review focuses on the research progress of ALK+ALCL, including the application and development of new therapeutic technologies, especially in terms of drug resistance. Meanwhile, we propose potential treatment strategies based on current research to facilitate clinical trials.